Effect of ART 2 treatment on biochemical profile during treatment of second line ART - Singh, Narendra; Varma, R. K.; Giri, Richa; Varma, Punit; Dwivedi, Seema; Kumar, Lalit (International Journal of Advances in Medicine, 2020)
Background: AIDS was the first recognized in U.S in summer of 1981 at centers for disease control and prevention reported the unexplained occurrence of pneumocystis jiroveci in previously healthy homosexual men in Los Angeles and Kaposi. First time in 1983 HIV syndrome was isolated from a patient of lymphadenopathy. Person with positive HIV serology who have ever had a CD4 lymphocyte count below 200celles/mcl and CD4 lymphocyte percentage below 14% are considered to have AIDS (CMDT 2017). Methods: This study was continuous longitudinal, prospective and retrospective, observational, at ART plus Centre, Kanpur K.P.S. institute of medicine (G.S.V.M. medical college) included the all patients on ART1 attending in Centre were screened for treatment failure based on clinical, immunological and virological criteria’s as decided by SACEP from 2016 to 2018. Results: Total numbers of patients are 118 among them 71 female and 47 males, age groups between 30-40 there are 54 patients. In study treatment with ART patients Hb levels more than 10%, Mean value before 10.85±1.31 and mean value after treatment was 10.5±1.31, TLC before 6970.94±6309.93 after treatment 6800.25±2522.99, Serum Bilirubin before and after treatment 0.69±0.49 and 0.95±1.13. Mean value of before and after treatment serum creatinin1.80±11.34 and 0.88±0.38. Conclusions: There is increased in serum creatinine and SGPT /SGOT and decrease in Hb levels in treatment of second line ART treatment so it should be monitored every monthly interval.